Changes in the Skin Proteome and Signs of Allostatic Overload Type 2, Chronic Stress, in Response to Repeated Overcrowding of Lumpfish (Cyclopterus lumpus L.) - Patel, Deepti M.; Brinchmann, Monica F.; Hanssen, Anna; Iversen, Martin H. (Frontiers in Marine Science, 2022)
Lumpfish (Cyclopterus lumpus L) is a North Atlantic species harvested for its roe and increasingly used as a cleanerfish in Atlantic salmon (Salmo salar L.) farming to remove salmon louse (Lepeophtheirus salmonis). In aquaculture, the health and welfare of fish depends on optimal levels of several biotic and abiotic factors. Crowding, a common abiotic stress factor in aquaculture practice, can affect the welfare and survival of fish. In this study, lumpfish was exposed to crowding stress daily at random timepoints for one month (stress group) or no crowding (control group). Blood and skin were sampled weekly for physiological parameter analysis and proteomics, respectively. Adrenocorticotropic hormone (ACTH) stimulation and dexamethasone (DEX) suppression test were conducted at the sampling timepoints. Gel-based proteomics coupled with liquid chromatography and tandem mass spectrometry (LC-MS/MS) was used to identify protein changes in skin tissues of lumpfish under crowding. The results indicated that the stress group showed signs of allostatic overload type 2 (chronic stress) due to oversensitivity to ACTH, and a reduced negative feedback system with increased baseline levels of cortisol. These chronic changes in the endocrine system promoted changes in secondary and tertiary stress responses as reduced osmoregulatory capacity and stunted growth, after 14 days of stress and onward. Calmodulin, guanine nucleotide binding protein subunit beta 2, glutathione-S-transferase Mu 3, fatty acid binding protein, heat shock cognate 70 kDa protein, keratin, histone H4 and 14-3-3 alpha/beta showed protein spot intensity changes compared with controls in lumpfish skin at one or several time points during the one month period of crowding stress. The differentially expressed proteins are related to several metabolic pathways and are involved in stress and immune responses. Overall, the study shows that lumpfish can suffer from chronic stress with possible dire consequences for the animal welfare.